18-Electron half-Heusler compound Ti0.75NiSb with intrinsic Ti vacancies as a promising thermoelectric material. Issue 17 (1st April 2022) - Luo, Feng; Wang, Jian; Zhu, Can; He, Xiong; Zhang, Shun; Wang, Jiafu; Liu, Hongxia; Sun, Zhigang
Abstract : Ti vacancies in 18-electron half-Heusler compound Ti0.75 NiSb cause lower lattice thermal conductivity. Abstract : Conventional 18-electron half-Heusler compounds with a high power factor are recognized as promising high-temperature thermoelectric materials, but the relatively high lattice thermal conductivity hinders their application. This work shows that a stoichiometric 19-electron TiNiSb compound is actually a combination of Ti0.75 NiSb and impurities. Through decreasing the Ti content in TiNiSb, the obtained 18-electron Ti0.75 NiSb has an increased Seebeck coefficient and a decreased electronic thermal conductivity due to the reduction of the carrier concentration. First-principles calculation shows that Ti0.75 NiSb is a semiconductor with an energy gap of approximately 0.65 eV at the Fermi level. The existence of intrinsic Ti vacancy defects and the larger Grüneisen parameter are contributors to the low thermal conductivity of Ti0.75 NiSb. Finally, Ti0.75 NiSb shows a low lattice thermal conductivity of 1.08 W m −1 K −1, which is less than those of most half-Heusler compounds, and a maximum ZT of 0.36 at 873 K. This work demonstrates that Ti0.75 NiSb is a promising thermoelectric material.